Intrauterine cytomegalovirus infection: a possible risk for cerebral palsy and related to its clinical features, neuroimaging findings: a retrospective study - H Xu; L Zhang; XY Xuan; M Zhu; J Tang; XK Zhao (BMC, 2020)
Abstract Background Abundant clinical evidences indicate that the increased risk of cerebral palsy (CP) may be associated with the intrauterine exposure to maternal infection. Cytomegalovirus (CMV) is a common cause of CP. However, little is known about the relationship between the intrauterine exposure of the fetus to CMV infection and CP. This study aims to explore the relationships between intrauterine CMV infection and clinical symptoms, classification, intelligence development and brain neuroimaging findings in children with CP. Methods In this study, 147 children with CP in recent 6 years were retrospectively analyzed (average age: 14.76 ± 3.07months; sex (M/F): 103/44). 148 children had CMV IgG and IgM positive sera identified by TORCH examination were selected as the control group (average age: 15.10 ± 3.21months; sex (M/F): 102/46), which also undergo the examination of CMV-DNA in urine. The age and sex of children in the control group were matched with those in the CP group. CMV-DNA in urine was detected by CMV fluorescence quantitative PCR, and t-test was performed to analyze the number of copies. For the CP group, standardized rehabilitation treatment was performed and the function of gross motor was evaluated by GMFM scale before and after treatment. The Gesell developmental scale (GDS) was used to assess the level of intellectual development. The classification of CP was conducted and the results of magnetic resonance imaging were analyzed. Finally, the correlations between the copy number of CMV-DNA and the clinical characteristics of children with CP were evaluated by the method of Pearson and Spearman correlation analysis. Results The level of CMV infection was negatively correlated with the developmental quotient (DQ) of children with CP. Negative association was found between the level of CMV infection and the level of the gross motor development. The level of CMV infection was positively related with the occurrence probability of spastic quadriplegia. However, no associations were found between the abnormalities of brain tissue and the number of CMV copies. Moreover, CMV infection might add the difficulty of the rehabilitation treatment. Conclusions CMV infection is a risk factor for the occurrence of CP in children. Pregnancy examination should be strengthened. Early detection and control of CMV infection may contribute to the rehabilitation of children with CP and reduce the disability and social burden.